Keanekaragaman Ikan Air Tawar Sistem Sungai Siret dan Vriendschap, Asmat–Papua - Henderite L. Ohee (Jurnal Biologi Papua, 2015)
Geologically southern part of New Guinea Island is the oldest part of the mainland and have most speciose of freshwater fish. Asmat is one area in Southern New Guinea where has some large river systems such as Siret and Vriendschap Rivers. There is not much information on freshwater fish diversity of the area. This study aim to know freshwater fish species of both river systems, in order to manage the area as conservation area by local government. Active fish collection method was applied to sample fish of Siret and Vriendschap River Systems. One seine net, 3.6 m length, 1.23 m in height, and with a mesh size of less than 0.5 cm, and traditional scoop net were used to collect fish. The Siret and Vriendschap freshwater fish fauna consist of 22 species in 18 genera and 15 families. Cochlefelis danielsi (Ariidae), Mogurnda cingulata (Eleotridae), Zenarchopterus novaeguineae (Hemiram-phidae), Melanotaenia ogilbyi (Melanotaenidae), Synaptura villosa (Soleidae) are endemic to Southern New Guinea. Spesifically, Mogurnda cingulata (Banded Gudgeon) and Melanotaenia ogilbyi (Ogilbyi’s Rainbowfish) have restricted distribution in Southern New Guinea. Further research in smaller stream and its tributaries might increase freshwater fish diversity of Asmat.Key words: Southern New Guinea, Asmat, freshwater fish